MOLECULAR WEIGHT PROFILE OF PROTEASE OF PINEAPPLE (Ananas comosus L.Merr) AND PAPAYA (Carica papaya L.) USING SDS-PAGE METHOD - Rizky Arcinthya Rachmania; Priyo Wahyudi; Aniza Mutia Wardani; Dini Rohmatul Insani (ALCHEMY Jurnal Penelitian Kimia, 2017)
A group of protease enzymes such as papain and bromelain is able to decipher the molecular structure of the protein into amino acids which will be very useful in many fields, especially in food and pharmaceutical industries. The objective of this study to determine the molecular weight profile of enzyme bromelain from pineapple bark (Ananas comosus L. Merr) and papain (Carica papaya L.) from papaya latex with different varieties using sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) method. The precipitation was performed with ammonium sulfate ((NH4)2SO4)) 60 % addition and dialysized using a cellophane tubing with a pore size of 12,000 Dalton. The molecular weight of enzyme solution were determined using SDS-PAGE. The analysis results of molecular weight of enzyme bromelain of Subang and Bogor varieties were not different and were about 30.654 kDa, as well as the molecular weight of enzyme papain and Sukma California varieties were also not different and were about 23.485 kDa. It can be concluded that the different varieties of fruit of pineapple and papaya had no effect on the molecular weight of enzyme papain and bromelain.